2020
DOI: 10.3390/cryst10060463
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Crystallization by Attachment

Abstract: Crystallization via particle attachment was used in a unified model for both classical and non-classical crystallization pathways, which have been widely observed in biomimetic mineralization and geological fields. However, much remains unknown about the detailed processes and driving mechanisms for the attachment. Here, we take calcite crystal as a model mineral to investigate the detailed attachment process using in situ Atomic Force Microscopy (AFM) force measurements and molecular dynamics simulations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another serious problem is the incorporation of different pollutants of different sizes are directly and indirectly that are inevitably incorporated into the matrix of this inorganic material [8]. Morphology is decisive and drastically governed by crystal growth parameters, in particular ZnO presents different, impressive and wonderful morphologies associated directly with the growth parameters as well as with the applied technique [9,10]. It is of utmost importance to understand the wide range of theoretical and experimental chemical and physical techniques in the synthesis of nanocrystals and in particular of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Another serious problem is the incorporation of different pollutants of different sizes are directly and indirectly that are inevitably incorporated into the matrix of this inorganic material [8]. Morphology is decisive and drastically governed by crystal growth parameters, in particular ZnO presents different, impressive and wonderful morphologies associated directly with the growth parameters as well as with the applied technique [9,10]. It is of utmost importance to understand the wide range of theoretical and experimental chemical and physical techniques in the synthesis of nanocrystals and in particular of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Nonclassical crystallization has been studied extensively by numerous researchers in the field of crystal growth. ,, Hwang et al showed that most nanoparticle building blocks generated in the gas-phase synthesis of thin films and nanostructures through chemical vapor deposition (CVD) are electrically charged and that the charges played a critical role in nonclassical crystallization . To emphasize the role of charges in nonclassical crystallization, the authors named the underlying theory the “theory of charged nanoparticles” …”
Section: Introductionmentioning
confidence: 99%